2020
DOI: 10.1124/dmd.120.090670
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Disposition of Coproporphyrin I (CPI) in Cynomolgus Monkeys and Mice: Pharmacokinetic Evidence to Support the Use of CPI to Inform the Potential for Organic Anion-Transporting Polypeptide Inhibition

Abstract: Despite a recent expansion in the recognition of the potential utility of coproporphyrin (CP) as an endogenous biomarker of organic anion-transporting polypeptide (OATP) 1B activity, there have been few detailed studies of CP's pharmacokinetic behavior and an overall poor understanding of its pharmacokinetic fate from tissues and excretion. Here, we describe the pharmacokinetics of octadeuterium-labeled coproporphyrin I (CPI-d8) in cynomolgus monkeys following oral and intravenous administration. CPI-d8 has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Our recent study indicated that CPI was subjected to limited oral absorption with bioavailability of less than 5% in monkeys and cyclosporin A did not significantly affect the CPI bioavailability (Gu et al, 2020), suggesting that the altered intestinal MRP2 is unlikely to affect the plasma concentration of endogenous CPI. The increased MRP2 expression in the liver after repeated RIF dosing ( Figure 4A) may contribute to enhanced CP clearance from the blood.…”
Section: Effects Of Rif On Oatp1b1 Gene Expression In the Liver Smalmentioning
confidence: 97%
See 1 more Smart Citation
“…Our recent study indicated that CPI was subjected to limited oral absorption with bioavailability of less than 5% in monkeys and cyclosporin A did not significantly affect the CPI bioavailability (Gu et al, 2020), suggesting that the altered intestinal MRP2 is unlikely to affect the plasma concentration of endogenous CPI. The increased MRP2 expression in the liver after repeated RIF dosing ( Figure 4A) may contribute to enhanced CP clearance from the blood.…”
Section: Effects Of Rif On Oatp1b1 Gene Expression In the Liver Smalmentioning
confidence: 97%
“…The final version may differ from this version. and OATP1B, respectively (Diczfalusy et al, 2011, Kasichayanula et al, 2014, Li et al, 2014, Tahara et al, 2019, Takehara et al, 2019, Gu et al, 2020. Therefore, 4βHC, CPI, and CPIII were selected as in vivo probes of CYP3A and OATP1B activities, and we studied the day-to-day change from predose plasma levels and throughout the entire study with the strong PXR activator RIF.…”
Section: Effects Of Rif On Oatp1b1 Gene Expression In the Liver Smalmentioning
confidence: 99%
“…where C blood , C LV , C LT , A bile , and A urine are the concentration (C) or amount (A) of CPI in the blood (central), liver vascular, liver tissue, bile, and urine compartments, respectively. The parameters 29 and low bioavailability of labeled CPI in monkeys, 30 this process was assumed to be insignificant for the PK of CPI and was not considered in the current model development.…”
Section: Cpi Population Pbpk Modelmentioning
confidence: 99%
“…Enterohepatic circulation of CPI was not considered in our model, supported by the recent studies. 29,30 For pragmatic reasons, concentration of rifampicin in the central compartment was used as inhibitory concentration affecting CPI CL active,u ; any potential rifampicin concentration gradient between blood and hepatic inlet was not considered. This assumption may potentially underestimate rifampicin OATP1B Ki, but the covariates estimated as relative changes are not likely to be sensitive to this assumption.…”
Section: Utility Of Model-informed Drug Development With Cpi Modelmentioning
confidence: 99%
See 1 more Smart Citation